Modified low-carbon cementitious material, preparation method and application thereof
Patent Information
- Application Number
- CN202611486765.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-23
- Publication Date
- 2026-10-30
AI Technical Summary
[0007]本发明的目的在于提供一种三元改性剂及一种改性低碳胶凝材料及其制备方法与应用,以解决现有技术中高掺量粉煤灰/矿渣复合体系早期水化缓慢、超细粉煤灰分散不良导致需水量增大与强度损失、常规激发剂难以同时兼顾早期强度、分散性与长期致密化,以及现有复合粉体系28 d活性指数难以稳定提升至110%以上的问题
1. 所述三元改性剂以两种有机分子与一种无机物构成三元协同体系,三种组分分别承担螯合-分散、桥接-促溶与晶核-填充功能,三者在水化过程中形成闭合作用回路:分子A通过邻位双齿配位形成的六元螯合环富集钙离子并在超细颗粒表面形成致密吸附层,实现颗粒分散与钙离子局部过饱和;分子B通过叔胺氮与铝离子/铁离子配位促进粉煤灰与矿渣玻璃体溶解,并向成核位点传输硅铝单体,同时以柔性链在纳米尺度界面形成桥接网络;无机物C提供异相成核位点并消耗过饱和,驱动回路持续运行,并与水化铝相反应生成碳铝酸钙稳定钙矾石。任一功能缺失均使回路中断、体系增益回落,由此使复合粉在等量替代水泥条件下获得高强度效率与致密化孔结构。
Smart Images

Figure CN123003165A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of low-carbon cementitious materials technology, and particularly relates to a modified low-carbon cementitious material, its preparation method and application. Background Technology
[0002] The cement industry is a major source of carbon emissions, and replacing cement clinker with a high proportion of industrial solid waste is an important way to reduce the carbon footprint of cementitious materials. Fly ash and granulated blast furnace slag powder are two types of stable and high-volume industrial by-products. Using them in combination with cement clinker can reduce clinker usage while maintaining cementitious properties. Fly ash is a low-calcium, silica-alumina pozzolanic material, and its activity depends on its glass content and specific surface area; blast furnace slag powder has potential hydraulic properties, and its activity increases with increasing specific surface area.
[0003] In existing technologies, there are three main approaches to improving the activity index of fly ash / slag composite powder: first, mechanical ultrafine grinding, which grinds fly ash to a higher specific surface area to increase the reaction contact area; second, chemical activation, which introduces activators such as sulfates, alkalis, and alkanolamines to promote vitreous dissolution; and third, the combined use of ultrafine grinding and activators. For example, Chinese patent application publication number CN102775085A discloses a fly ash composite product and its preparation method, which involves co-grinding fly ash and slag to a specific surface area of not less than 550 m². 2 / kg, and with the addition of an activity activator composed of sodium sulfate, quicklime, and polycarboxylate superplasticizer, its activity index at 3d, 7d, and 28d reached 85%, 90%, and 105%, respectively. Chinese Patent Publication No. CN117326808B discloses an ultrafine cementitious material and its preparation method and application, which involves composite grinding of slag, steel slag, and fly ash to a specific surface area of 720-740 m². 2 / kg and add solubilizing and activating agents. Chinese Patent Application Publication No. CN115784703A discloses a high-strength mine filling cementitious material based on solid waste and its preparation method, which uses steel slag, magnesium slag, fly ash, slag and other raw materials and adds modifiers for use in low-strength mine filling systems.
[0004] However, the aforementioned existing technologies still have the following technical problems. First, high-volume fly ash / slag composite systems with a cement substitution rate of 50% or higher exhibit slow early hydration; the 28-day pozzolanic reaction degree of fly ash is typically less than 40%, resulting in lower early strength than pure cement systems, and a 3-day strength ratio generally below 90%. Second, fly ash needs to be ultra-finely ground to 550-600 μm. 2The surface area increases with weight, leading to increased particle agglomeration and a water requirement ratio that can rise to over 115%. Poor dispersion results in decreased workability and strength loss, and the activity gain from ultrafine grinding is partially offset by dispersion losses. Third, conventional chemical activators such as sulfates, alkalis, and triethanolamine have simple mechanisms of action and narrow dosage windows, making it difficult to simultaneously address the three objectives of early strength, particle dispersion, and long-term densification. Sulfate and alkali activators also pose a risk of introducing excessive alkali, leading to alkali-aggregate reaction and workability deterioration. Fourth, the 28-day activity index of existing composite powder and activator combinations generally does not exceed 105%, failing to stably increase to over 110%, and lacks sensitive design targeting the molecular structure-performance relationship of activators, making it difficult to precisely optimize the activation effect through molecular structure regulation.
[0005] Therefore, there is an urgent need for a modified low-carbon cementitious material and its preparation method that achieves an activity index of 110%-120% after 28 days under the condition of a cement substitution rate of 50%, good dispersibility of ultrafine powder, no increase in water demand ratio, accelerated early hydration, dense pore structure, and controllable setting time.
[0006] It should be noted that the primary value of the high-volume industrial solid waste low-carbon cementitious material targeted by this invention lies in the carbon reduction effect brought about by reducing the amount of clinker used. In the context of increasingly stringent carbon emission constraints, the carbon reduction value is taken as the main consideration. Summary of the Invention
[0007] The purpose of this invention is to provide a ternary modifier and a modified low-carbon cementitious material, along with their preparation method and application, to solve the problems in existing technologies such as slow early hydration of high-volume fly ash / slag composite systems, poor dispersion of ultrafine fly ash leading to increased water demand and strength loss, the difficulty of conventional activators simultaneously achieving early strength, dispersibility, and long-term densification, and the difficulty in consistently increasing the 28-day activity index of existing composite powder systems to over 110%. To achieve the above objectives, this invention adopts the following technical solution.
[0008] In a first aspect, the present invention provides a ternary modifier, composed of molecule A, molecule B, and inorganic compound C; wherein molecule A is 4,4'-dihydroxy-[1,1'-biphenyl]-3,3',5,5'-tetracarboxylic acid, and the molecular formula C is... 16 H 10 O 10With a relative molecular mass of 362.25, its molecule contains four aromatic carboxyl groups, two phenolic hydroxyl groups, and a rigid biphenyl conjugated skeleton. The 4,4'-phenolic hydroxyl groups and the 3,3' / 5,5'-aromatic carboxyl groups are adjacent to each other and form an ortho-bident coordination unit. The coordination atom chain is OCCCO, which closes into a six-membered chelate ring when chelated with calcium ions. Molecule B is N,N'-bis(carboxymethyl)-N,N'-bis(2-hydroxyethyl)-1,6-hexanediamine, with the molecular formula C. 14 H 28 N₂O₆, with a relative molecular mass of 320.38, contains two tertiary amine nitrogen atoms, two carboxymethyl groups, two hydroxyethyl groups, and a flexible C₆ linear backbone; the inorganic component C is nano-calcium carbonate with an average particle size of 50-100 nm and a specific surface area of not less than 20 m². 2 / g, calcium carbonate content not less than 98%; the mass ratio of molecule A to molecule B is (1-2):1, and the total amount of molecule A and molecule B is in the mass ratio of the inorganic substance C to the total amount of inorganic substance C is (2-3):1.
[0009] Secondly, the present invention provides a modified low-carbon cementitious material, comprising, by weight: 30-70 parts of ultrafine fly ash; 30-70 parts of ultrafine slag powder, wherein the total weight of the ultrafine fly ash and the ultrafine slag powder is 100 parts, i.e., the mass ratio of the ultrafine fly ash to the ultrafine slag powder is (3-7):(7-3); and 0.5-2.0 parts of a ternary modifier, wherein the ternary modifier accounts for 0.5%-2.0% of the total mass of the ultrafine fly ash and the ultrafine slag powder.
[0010] The ternary modifier is the ternary modifier described in the first aspect.
[0011] In one embodiment, the mass ratio of molecule A to molecule B is (1-2):1, and the total amount of molecule A and molecule B is in the mass ratio of the inorganic substance C to the total amount of molecule C is (2-3):1.
[0012] In one embodiment, the ultrafine fly ash is type F low-calcium fly ash with a Blaine surface area of 550-600 m². 2 / kg, 45 μm sieve residue not greater than 5%, loss on ignition not greater than 5%.
[0013] In one embodiment, the ultrafine slag powder has a glass content of not less than 85% and a Blaine specific surface area of 400-600 m². 2 / kg.
[0014] In one embodiment, the mass ratio of the ultrafine fly ash to the ultrafine slag powder is (4-6):(6-4).
[0015] In one embodiment, the ternary modifier accounts for 1.0%-2.0% of the total mass of the ultrafine fly ash and the ultrafine slag powder.
[0016] In one embodiment, the mass ratio of molecule A to molecule B is 1:1.
[0017] In one embodiment, the total amount of molecule A and molecule B is in a mass ratio of 2:1 to the inorganic substance C, that is, the mass ratio of molecule A, molecule B and inorganic substance C in the ternary modifier is 1:1:1.
[0018] In one embodiment, during the preparation of the ternary modifier, the dry mixing speed is 800-1200 r / min and the dry mixing time is 5-15 min.
[0019] In one embodiment, the dry mixing time in the preparation of the ternary modifier is 8-12 min.
[0020] In one embodiment, the co-grinding is performed using a planetary ball mill with a ball-to-material mass ratio of (6-10):1 and a co-grinding time of 5-30 min.
[0021] In one embodiment, the modified low-carbon cementitious material is used to replace 50% of cement in the preparation of mortar or concrete, with a water-cement ratio of 0.50, a standard curing temperature of 20 ± 1 ℃, and a relative humidity of not less than 90%.
[0022] Thirdly, the present invention also provides a method for preparing the above-mentioned modified low-carbon cementitious material, comprising the following steps: (1) preparation of ternary modifier: mixing the molecule A, the molecule B and the inorganic substance C in proportion, dry mixing for 5-15 min to obtain ternary modifier; (2) premixing and co-grinding: mixing the ultrafine fly ash, the ultrafine slag powder and the ternary modifier, premixing for 5-15 min to obtain premixed material, co-grinding the premixed material in a planetary ball mill for 5-30 min, sieving the discharged material to obtain modified low-carbon cementitious material.
[0023] The preparation method uses mechanical-chemical co-milling to uniformly coat the ternary modifier on the surface of the ultrafine powder and further refine it, thereby improving particle dispersion. The two-step mixing of premixing and co-milling ensures the uniform distribution of trace components of the ternary modifier in the composite powder and avoids uneven dispersion caused by post-addition. The organic molecules in the ternary modifier play a role in grinding and dispersing during the co-milling process, reducing the tendency of agglomeration.
[0024] Fourthly, the present invention also provides the application of the above-mentioned modified low-carbon cementitious material in the preparation of cement mortar, concrete or precast components, wherein the modified low-carbon cementitious material replaces 50% of cement in equal amounts.
[0025] The modified low-carbon cementitious material provided by this invention has the following beneficial effects: 1. The ternary modifier comprises a synergistic system of two organic molecules and one inorganic substance. The three components respectively perform chelation-dispersion, bridging-solution promotion, and nucleation-filling functions, forming a closed-loop interaction during hydration: molecule A enriches calcium ions through a six-membered chelate ring formed by ortho-bidate coordination, creating a dense adsorption layer on the surface of ultrafine particles, achieving particle dispersion and localized calcium ion supersaturation; molecule B promotes the dissolution of fly ash and slag glass through coordination of tertiary amine nitrogen with aluminum / iron ions, and transports silicon-aluminum monomers to nucleation sites, while simultaneously forming a bridging network at the nanoscale interface with flexible chains; inorganic substance C provides heterogeneous nucleation sites and consumes supersaturation, driving the continuous operation of the loop, and reacts with the hydrated aluminum phase to generate calcium aluminate stable ettringite. The loss of any function interrupts the loop and reduces the system gain, thereby enabling the composite powder to achieve high strength efficiency and a dense porous structure under conditions of equivalent cement substitution.
[0026] 2. The organic molecules in the ternary modifier exhibit structural selectivity: the ortho-phenolic hydroxyl-carboxyl bidentate coordination unit of molecule A, with a coordination atom chain OCCCO, forms a closed six-membered chelate ring; the C6 bridging chain length and the hydroxyethyl hydrogen bond donor of molecule B are both structure-dependent factors for system gain. Even slight changes in structural elements can lead to a decrease in performance, thus making the modification effect dependent on the molecular structure.
[0027] 3. The ternary modifier improves the strength efficiency of the composite powder, reduces the amount of cementitious materials under the same strength conditions, thereby reducing the equivalent clinker and carbon footprint, and achieving low carbonization; at the same time, it improves the dispersibility of ultrafine powder, reduces water demand, and keeps the setting time controllable, making it suitable for various application scenarios such as mortar, concrete and precast components. Attached Figure Description
[0028] Figure 1 Here are the structural formulas of molecules A and B of the present invention; wherein, 1A is molecule A and 1B is molecule B.
[0029] Figure 2 This is a schematic diagram of the process flow from preparation to application of the modified low-carbon cementitious material of this invention.
[0030] Figure 3 The spectrum of molecule A of the present invention is shown below; wherein, 3A is the Fourier transform infrared spectrum, 3B is the nuclear magnetic resonance carbon spectrum, and 3C is the mass spectrum.
[0031] Figure 4 The spectrum of molecule B of the present invention is shown below; wherein, 4A is the Fourier transform infrared spectrum, 4B is the nuclear magnetic resonance carbon spectrum, and 4C is the mass spectrum. Detailed Implementation
[0032] The following examples and comparative examples are used to illustrate the technical solutions of the present invention, but the implementation of the present invention is not limited thereto. Unless otherwise specified, the raw materials used in the examples and comparative examples are all commercially available industrial products or analytical grade reagents; the test methods, specimen specifications, and curing conditions used are all the same to ensure data comparability. In the examples and comparative examples, the total amount of ultrafine fly ash and ultrafine slag powder is 100 parts; the activity index is determined according to Appendix A of GB / T 18046-2017; the tested powder is fly ash-slag composite powder; the test mortar uses the tested composite powder to replace 50% of the reference cement; the compressive strength of the mortar is determined according to GB / T 17671-2021; the setting time is determined according to GB / T 1346-2011; the water requirement ratio is determined according to GB / T 1596-2017; and the fluidity ratio is determined according to Appendix A of GB / T 18046-2017. Unless otherwise specified, the curing regime is standard curing.
[0033] Molecules A and B were synthesized according to Preparation Example 1 and Preparation Example 2, respectively; inorganic compound C was commercially available industrial-grade nano-calcium carbonate; the ternary modifier TGM was prepared by dry mixing of molecules A, B, and inorganic compound C according to Preparation Example 3. Hereinafter, 4,4'-dihydroxy-[1,1'-biphenyl]-3,3',5,5'-tetracarboxylic acid will be referred to as molecule A, N,N'-bis(carboxymethyl)-N,N'-bis(2-hydroxyethyl)-1,6-hexanediamine as molecule B, nano-calcium carbonate as inorganic compound C, and the ternary modifier as TGM.
[0034] The main raw materials and reagents used in this plan are as follows: (1) Cementitious material raw materials: Ultrafine fly ash: Class F low-calcium fly ash, mechanically ground to a Blaine specific surface area of 550-600 m² 2 / kg, 45 μm sieve residue not greater than 5%, loss on ignition not greater than 5%; ultrafine slag powder: glass content not less than 85%, Blaine specific surface area 400-600 m² 2 / kg; Reference cement: P·O 42.5 reference cement conforming to GB 8076; ISO standard sand.
[0035] (2) Ternary modifier components: Molecule A: self-made according to Preparation Example 1, with a content of not less than 98%; Molecule B: self-made according to Preparation Example 2, with a content of not less than 98%; Nano-calcium carbonate: commercially available industrial grade, with a calcium carbonate content of not less than 98%, an average particle size of 50-100 nm, and a specific surface area of not less than 20 m². 2 / g.
[0036] (3) Reagents for the synthesis of molecule A: 4,4'-dihydroxybiphenyl (biphenyl hydroquinone) content not less than 99%; anhydrous potassium carbonate; dimethyl sulfate content not less than 98%, iodomethane as an alternative; N,N-dimethylformamide (DMF); bromine; reduced iron powder; chloroform; cuprous cyanide; ferric chloride; hydrochloric acid; potassium hydroxide; anhydrous ethanol; 1.0 mol / L boron tribromide dichloromethane solution; dichloromethane; methanol; sodium hydroxide; activated carbon.
[0037] (4) Reagents for the synthesis of molecule B: 1,6-hexanediamine with a content of not less than 99.5%; industrial grade ethylene oxide with a content of not less than 99.5%, 2-chloroethanol as an alternative; chloroacetic acid with a content of not less than 98%; 40% and 20% sodium hydroxide aqueous solutions; acetone; concentrated hydrochloric acid.
[0038] (5) Reagents for synthesizing structural analogs: ethylenediamine content not less than 99%; 37% formaldehyde aqueous solution; sodium borohydride; methanol; dichloromethane.
[0039] (6) Comparative reagents: Triethanolamine (TEA) content not less than 99%; commercially available 400-800 mesh heavy calcium carbonate, D50 about 5 μm, calcium carbonate content not less than 98%.
[0040] Preparation Example 1 Molecule A (4,4'-dihydroxy-[1,1'-biphenyl]-3,3',5,5'-tetracarboxylic acid) was synthesized in the following five steps: phenolic hydroxyl methylation, electrophilic bromination at the 3,3',5,5' position, Rosenmund-von Braun cyanation, nitrile basic hydrolysis, and demethylation with methyl ether. The specific operations for each step are as follows.
[0041] Step 1: Preparation of 4,4'-dimethoxybiphenyl (phenolic hydroxymethylation): To a 1000 mL three-necked flask equipped with an organic olive stirrer, a reflux condenser, and a thermometer, add 37.2 g of 4,4'-dihydroxybiphenyl, 82.9 g of anhydrous potassium carbonate, and 250 mL of DMF. With stirring, add 53.0 g of dimethyl sulfate dropwise at room temperature, maintaining the internal temperature below 30 °C throughout the addition, which takes approximately 40 min. After the addition is complete, raise the temperature to 80 °C and maintain the reaction for 8 h. Monitor the reaction by TLC using petroleum ether:ethyl acetate (10:1) as the developing solvent; the Rf is approximately 0.45 until the starting material spot disappears. Cool to room temperature and slowly pour the reaction mixture into 500 mL of ice water, precipitating a white solid. Filter the solid, wash the filter cake sequentially with 3 × 150 mL of pure water until neutral, and dry under vacuum at 50 °C for 6 h to obtain 38.5 g of white flaky solid 4,4'-dimethoxybiphenyl (90% yield). Recrystallize from ethanol to obtain an analytical grade sample with a melting point of 172–174 °C. Alternative method: Replacing dimethyl sulfate with 59.6 g of iodomethane, reacting in DMF at 60 °C for 8 h, yielded comparable results. The structures of each intermediate were confirmed by 1H NMR and IR spectroscopy.
[0042] Step 2, Preparation of 3,3',5,5'-tetrabromo-4,4'-dimethoxybiphenyl (electrophilic bromination): Add 21.4 g of the product from step one, 0.30 g of reduced iron powder, and 250 mL of chloroform to a 500 mL three-necked flask equipped with an organic olive stirrer, a dropping funnel, and a reflux condenser, with the tail gas connected to a 5% NaOH alkaline absorption flask. Cool the flask to 0-5 °C in an ice bath, and slowly add 70.3 g of bromine dropwise over 1 h, protecting the flask from light. After the addition is complete, remove the ice bath, stir at room temperature for 2 h, and then heat under reflux for 5 h at an internal temperature of approximately 61 °C. Monitor the reaction by TLC using petroleum ether:ethyl acetate = 20:1 as the developing solvent until the starting material disappears. The reaction mixture was cooled to room temperature, and excess bromine was quenched by slowly pouring it into 300 mL of a 10% sodium bisulfite aqueous solution. The red color faded to colorless. The mixture was separated, and the aqueous phase was extracted with 2 × 80 mL of chloroform. The combined organic phases were washed successively with 2 × 150 mL of saturated sodium bicarbonate aqueous solution and 150 mL of pure water, dried over anhydrous sodium sulfate, filtered, concentrated under reduced pressure to approximately 80 mL, cooled to 0 °C to crystallize, filtered, and recrystallized from ethyl acetate to give 36.0 g of a white solid, with a yield of 68%. The molecule was highly symmetrical, and its structure was confirmed by 1H NMR and IR spectroscopy.
[0043] Step 3, Preparation of 3,3',5,5'-tetracyano-4,4'-dimethoxybiphenyl (Rosenmund-von Braun cyanidation): To a 500 mL three-necked flask equipped with an organic olive stirrer, a reflux condenser, and a thermometer, add 26.5 g of the product from step two, 26.9 g of cuprous cyanide, and 200 mL of anhydrous DMF. Heat to 150-160 °C and reflux for 14 h under nitrogen protection, monitoring with TLC using petroleum ether:ethyl acetate = 5:1 as the developing solvent until the starting material disappears. Cool slightly to 80 °C, and pour the reaction mixture into a 60 °C preheated ferric chloride solution prepared with 40 g of FeCl3·6H2O, 25 mL of concentrated hydrochloric acid, and 300 mL of pure water. Stir at 60-80 °C for 1 h to break down the copper-cyanide complex. Filter while hot, and wash the filter cake successively with 2 × 100 mL of 5% dilute ammonia and 3 × 150 mL of pure water. Dry under vacuum at 60 °C for 8 h to obtain a yellowish-brown crude solid. Recrystallize the crude product from DMF-water to obtain 10.0 g of a pale yellow solid, yielding 64%. Complete cyanidation was confirmed by nuclear magnetic resonance hydrogen spectroscopy and infrared spectroscopy.
[0044] Step 4: Preparation of 4,4'-dimethoxy-[1,1'-biphenyl]-3,3',5,5'-tetracarboxylic acid (nitrile alkaline hydrolysis): To a 250 mL three-necked flask equipped with an organic olive stirrer and a reflux condenser, add 9.4 g of the product from step three, 16.8 g of potassium hydroxide, 60 mL of pure water, and 120 mL of anhydrous ethanol. Heat under reflux for 20 h at an internal temperature of approximately 78 °C. Monitor by TLC using n-butanol:acetic acid:water = 4:1:1 as the developing solvent until the nitrile point disappears. Concentrate under reduced pressure to remove ethanol. Cool the remaining aqueous phase in an ice bath and acidify with 6 mol / L hydrochloric acid dropwise to pH 1-2 with stirring. A large amount of white solid precipitates. Continue stirring for 30 min, filter, wash the filter cake with pure water until the filtrate is neutral, and dry under vacuum at 60 °C for 10 h to obtain 10.5 g of white powder, with a yield of 90%. This compound, structural analog A′, is 4,4'-dimethoxy-[1,1'-biphenyl]-3,3',5,5'-tetracarboxylic acid with a relative molecular mass of 390.30. Its preparation is described in Preparation Example 4.
[0045] Step 5, Preparation of molecule A (demethylation of methyl ether): Add 7.8 g of the product from step four and 200 mL of anhydrous dichloromethane to a 500 mL three-necked flask equipped with an organic olive stirrer, a constant-pressure dropping funnel, a cryostat, and nitrogen protection. Purge the flask three times with nitrogen. Cool to -78 °C using a dry ice-acetone bath. Add 160 mL of a 1.0 mol / L boron tribromide solution in dichloromethane dropwise over 40 min, maintaining the internal temperature no higher than -70 °C during the addition. After the addition is complete, allow the flask to rise naturally to room temperature, stir for 12 h, and then heat under reflux for 5 h, maintaining an internal temperature of approximately 40 °C. Monitor the flask using TLC with ethyl acetate:methanol:formic acid = 8:1:0.1 as the developing solvent until the starting material spot disappears. Cool to 0 °C in an ice bath, and slowly add 60 mL of methanol to quench excess BBr3 (exothermic, generating HBr, requiring an alkaline absorption device). Add 100 mL of water, concentrate under reduced pressure to remove dichloromethane and methanol, filter the residual aqueous phase, and wash the filter cake with 3 × 100 mL of pure water. The crude product was dissolved in 60 mL of 5% sodium hydroxide aqueous solution, 2 g of activated carbon was added, and the mixture was stirred at 60 °C for 30 min to decolorize. The mixture was filtered while hot, and the filtrate was cooled to 0 °C. 6 mol / L hydrochloric acid was added dropwise to acidify the solution to pH 1-2, and a pale yellow solid precipitated. The solid was filtered, washed with pure water until neutral, and dried under vacuum at 50 °C for 12 h to obtain 5.6 g of pale yellow to white powder molecule A, with a yield of 78%.
[0046] Summary of Preparation Example 1: Starting with 37.2 g of biphenyl hydroquinone, molecule A was synthesized through five steps: methylation, bromination, cyanation, hydrolysis, and demethylation. The yields of each step were 90% for step one, 68% for step two, 64% for step three, 90% for step four, and 78% for step five. Multiplying the yields of each step, i.e., when the intermediates are fully carried forward, the total yield is approximately 28%, theoretically yielding approximately 20 g of molecule A from 0.200 mol of starting material. In this preparation example, the materials were processed in steps to facilitate the step-by-step characterization of intermediates. Step two used 21.4 g / 38.5 g of the product from step one; step three used 26.5 g / 36.0 g of the product from step two; step four used 9.4 g / 10.0 g of the product from step three; and step five used 7.8 g / 10.5 g of the product from step four. Therefore, the actual yield of molecule A obtained from this demonstration batch after five steps was approximately 5.6 g. This 5.6 g represents the actual yield under step-by-step processing and is not the same as the total yield of 28% under full-load forward processing; however, the two figures are consistent and not contradictory. Each intermediate can be characterized step-by-step, and the route can be repeated. The infrared spectrum, carbon NMR spectrum, mass spectrometry, and their correspondence with the structure of molecule A are shown in [reference needed]. Figure 3 And graph-by-graph analysis.
[0047] Preparation Example 2 Molecule B (N,N'-bis(carboxymethyl)-N,N'-bis(2-hydroxyethyl)-1,6-hexanediamine) was synthesized in two steps: hydroxyethylation and carboxymethylation. The specific operations for each step are as follows.
[0048] Step 1: Preparation of N,N'-bis(2-hydroxyethyl)-1,6-hexanediamine (hydroxyethylation): Method A, Main Route Ethylene Oxide Method: Add 116.2 g of 1,6-hexanediamine and 60 mL of pure water to a 500 mL stainless steel high-pressure reactor. After sealing, purge with nitrogen three times. Heat to 60 °C with stirring. Begin batching 90.3 g of ethylene oxide, controlling the rate of introduction to maintain an internal temperature of 60-90 °C and a reactor pressure not exceeding 0.5 MPa, completing the process in approximately 3-4 hours. After completion, maintain the temperature at 80 °C for 4 hours until the pressure no longer decreases. Cool to below 30 °C, slowly vent, and purge with nitrogen for 30 minutes to remove residual ethylene oxide. Concentrate the reaction solution under reduced pressure to remove water, yielding 178 g of a light yellow viscous oily liquid, with a yield of 87% and a purity of not less than 90%, which is directly used in the next step.
[0049] Method B, Alternative Route: 2-Chloroethanol Method: Add 116.2 g of 1,6-hexanediamine, 169.1 g of 2-chloroethanol, 84.0 g of sodium hydroxide, and 300 mL of pure water to a 1000 mL three-necked flask equipped with an organic olive stirrer and a reflux condenser. Heat under reflux for 12 h at an internal temperature of 90-95 °C. Cool and concentrate under reduced pressure to approximately 150 mL. Add 400 mL of anhydrous ethanol to precipitate sodium chloride. Filter, and concentrate the filtrate under reduced pressure to obtain approximately 160 g of a pale yellow, viscous, oily crude product, with a yield of 78% and a purity of not less than 88%. This product is used directly in the next step. The structure of the intermediate was confirmed by 1H NMR and IR spectroscopy.
[0050] Step 2, Preparation of molecule B (carboxymethylation): (1) Preparation of sodium chloroacetate solution: Add 103.9 g of chloroacetic acid and 150 mL of pure water to a 500 mL beaker. Under ice bath cooling, slowly add about 110 g of 40% sodium hydroxide aqueous solution and neutralize to pH 7-8 to obtain sodium chloroacetate aqueous solution for later use.
[0051] (2) Add 102.2 g of the product from step one and 200 mL of pure water to a 1000 mL three-necked flask equipped with an organic olive stirrer, thermometer and reflux condenser, and stir to dissolve. Add the above sodium chloroacetate solution, heat to 65 °C, and during the reaction, add about 66 g of 20% sodium hydroxide aqueous solution dropwise to maintain the pH of the system at 10-11. Keep the reaction at this temperature for 7 h, and monitor the secondary amine until it disappears by TLC with n-butanol:acetic acid:water = 4:1:1 as the developing solvent and by titration with ninhydrin or free amine. Cool to room temperature, acidify with concentrated hydrochloric acid to pH 3-4, concentrate under reduced pressure to a viscous consistency of about 150 mL, add 500 mL of anhydrous ethanol and stir for 30 min to precipitate sodium chloride, filter, concentrate the filtrate under reduced pressure to obtain a light yellow viscous crude product; dissolve the crude product in about 100 mL of pure water, slowly add 400 mL of acetone and precipitate a solid at 0 °C, filter, wash with 2 × 80 mL of acetone, and dry under vacuum at 40 °C for 8 h to obtain a white to light yellow solid, molecular B, 128 g, yield 80%.
[0052] Summary of Preparation Example 2: Starting with 116.2 g of 1,6-hexanediamine, molecule B was synthesized via two steps: hydroxyethylation and carboxymethylation. The hydroxyethylation yield was 87%, and the carboxymethylation yield was 80%. Multiplying the yields of both steps (i.e., when all intermediates are fully carried forward), the total yield is approximately 70%, theoretically yielding approximately 224 g of molecule B from 1,000 mol of starting material. In this preparation, 102.2 g of the product from step one was added to the carboxymethylation process. This amount represents approximately 57% of the 178 g product from that step, yielding 128 g of molecule B, i.e., a carboxymethylation yield of 80% based on the intermediates added. This 128 g represents the actual output of this demonstration batch under stepwise feeding, and is not the same as the 70% total yield achieved with full forward carrying forward; however, the two are consistent and not contradictory. The route can be repeated. The infrared spectrum, carbon NMR spectrum, mass spectrometry, and their correspondence with the structure of molecule B are shown in [reference needed]. Figure 4 And graph-by-graph analysis.
[0053] Preparation Example 3 TGM, or ternary modifier, is prepared according to the mass ratio of molecule A: molecule B: inorganic substance C = 1:1:1, as follows: (1) Raw material pretreatment: Molecular A obtained in Preparation Example 1 and Molecular B obtained in Preparation Example 2 were dried in a vacuum drying oven at 60 °C for 4 h to constant weight. After cooling, they were pulverized and passed through a 200-mesh sieve to obtain dry powder for later use. Nano calcium carbonate was dried at 60 °C for 2 h before use.
[0054] (2) Dry mixing: Weigh 100.0 g each of molecule A, molecule B, and nano calcium carbonate according to the mass ratio, and add them together to a plow-type or twin-shaft paddle-type high-speed mixer. Dry mix at 1000 r / min for 10 min. Discharge the material, pass it through a 100-mesh sieve to break up any clumps, and obtain approximately 296 g of light gray uniform powder TGM. Store in a sealed, moisture-proof container.
[0055] (3) Quality control: The uniformity of TGM is tested by taking samples from the top, middle and bottom points and burning them at 550 °C for 2 h using the loss on ignition method. The relative deviation of the loss on ignition at each point is no more than 3% to be considered qualified.
[0056] (4) Small-batch preparation of TGM with different ratios: TGM with different ratios / different components required for Example 5 and each comparative example were prepared in small batches according to the same pretreatment and dry mixing process as described in (1) and (2) above, with each batch containing no less than 5 g to ensure uniform mixing; the viscous liquid component triethanolamine was first ground and adsorbed with an equal amount of powder component and then dry mixed.
[0057] Summary of Preparation Example 3: TGM is a physical dry-mixed complex of molecule A, molecule B, and nano-calcium carbonate, without chemical synthesis. The key control points are that the fineness of the raw materials is no more than 200 mesh, and the mixing speed and time. Example 1 used a 1:1:1 mass ratio, 1000 r / min, and 10 min.
[0058] Preparation Example 4 Preparation of structural analog A′ (4,4'-dimethoxy-[1,1'-biphenyl]-3,3',5,5'-tetracarboxylic acid): A′ is the intermediate product obtained in step four of Preparation Example 1. Procedure: All steps are the same as those for the synthesis of molecule A in Preparation Example 1, but step five, i.e., the BBr3 demethylation step, is omitted. The 4,4'-dimethoxy-[1,1'-biphenyl]-3,3',5,5'-tetracarboxylic acid obtained in step four is used directly as A′. The relative molecular mass is 390.30, and it is a white powder. The structure was confirmed by 1H NMR, IR, and mass spectrometry. The only structural difference from molecule A is that the 4,4'-phenolic hydroxyl group is etherified with a methyl group, the hydroxyl group is converted to a methoxy group, and the ortho-bident coordination unit composed of the ortho-phenolic hydroxyl group and the carboxyl group is lost. Its coordination chain is OCCCO.
[0059] Preparation Example 5 Preparation of structural analog B′ (N,N'-bis(carboxymethyl)-N,N'-bis(2-hydroxyethyl)ethylenediamine): All steps were the same as those for the synthesis of molecule B in Preparation Example 2, except that 1,6-hexanediamine in step one was replaced with an equimolar amount of ethylenediamine. The hydroxyethylation and carboxymethylation operations were exactly the same, using 2.05 equivalents of ethylene oxide or 2.1 equivalents of 2-chloroethanol and 2.2 equivalents of chloroacetic acid, respectively, at pH 10-11 and 65 °C for 7 h. B′ was obtained: Molecular formula C 10 H 20N₂O₆, with a relative molecular mass of 264.28, achieved a combined yield of approximately 65%-75% in two steps. Its structure was confirmed by 1H NMR and mass spectrometry. The only structural difference from molecule B is that the C6 flexible chain is shortened to C2, the nitrogen-nitrogen end distance is reduced from approximately 0.9-1.0 nm to approximately 0.4 nm, and the bridging chain length is shortened by approximately 60%. This results in a decreased bridging / stitching coverage ability at nanoscale interfaces such as the surface of nano-calcium carbonate and between CSH gel / adsorption layers.
[0060] Preparation Example 6 The preparation of structural analog B″ (N,N'-bis(carboxymethyl)-N,N'-dimethyl-1,6-hexanediamine) involves two steps: first N-methylation, then carboxymethylation.
[0061] Step 1: Preparation of N,N'-dimethyl-1,6-hexanediamine (formaldehyde reducing amination): Add 58.1 g of 1,6-hexanediamine and 300 mL of anhydrous methanol to a 1000 mL three-necked flask equipped with an organic olive stirrer, thermometer, and constant-pressure dropping funnel. Cool to 0-5 °C in an ice bath. Slowly add 85.2 g of 37% formaldehyde aqueous solution dropwise over 30 min with stirring, maintaining an internal temperature of 0-10 °C during the addition. After the addition is complete, stir at room temperature for 1 h. Cool again to 0 °C, and add 22.7 g of sodium borohydride in portions over 1 h, controlling the internal temperature to not exceed 15 °C. After the addition is complete, stir at room temperature for 2 h. Methanol was removed by vacuum concentration. The residue was then treated with 150 mL of pure water and alkalized with 30% sodium hydroxide aqueous solution to a pH not lower than 12. Extraction was performed with 3 × 120 mL of dichloromethane. The organic phases were combined, dried over anhydrous sodium sulfate, filtered, and distilled under vacuum at 10 mmHg. The fraction collected at 88–95 °C yielded 52 g of N,N'-dimethyl-1,6-hexanediamine, a colorless oily liquid, with a yield of 72%. Formaldehyde was used at a concentration of 1.05 eq per nitrogen, introducing only one methyl group and forming a secondary amine. Excess formaldehyde would form a tetramethyl tertiary amine, which could not be further carboxymethylated. The intermediate's structure was confirmed by 1H NMR spectroscopy.
[0062] Step 2, Preparation of B″ (Carboxymethylation): All operations are the same as the carboxymethylation in Step 2 of Preparation Example 2, except that N,N'-bis(2-hydroxyethyl)-1,6-hexanediamine is replaced with an equimolar amount of 72.1 g of N,N'-dimethyl-1,6-hexanediamine and 103.9 g of chloroacetic acid. The pH is 10-11, the incubation period is 65 °C, and the post-treatment is the same. The result is B″: Molecular formula C 12 H 24 N₂O₄, with a relative molecular mass of 260.33 and a yield of 75%, was characterized by 1H NMR and mass spectrometry, and showed no characteristic signal of hydroxyethyl. The only structural difference from molecule B is that the hydroxyethyl group is replaced by a methyl group, thus losing the hydroxyl hydrogen bond donor.
[0063] Example 1
[0064] Step 1, S1 premix: Weigh 375.0 g of ultrafine fly ash and 375.0 g of ultrafine slag powder, add 11.25 g of TGM ternary modifier obtained in Preparation Example 3, accounting for 1.5% of the total mass of the composite powder, place in a V-type mixer, premix at 300 r / min for 10 min, and obtain 761.25 g of premix.
[0065] Step 2, S2 co-milling: Divide the premix into 6 portions, each approximately 126.9 g, and place each portion into a 500 mL stainless steel container of a planetary ball mill. Add 1015 g / container of Φ10 mm stainless steel grinding balls, with a ball-to-material mass ratio of 1015:126.9 ≈ 8:1. Co-mill at 350 r / min for 20 min, intermittently: stop for 1 min of cooling after every 5 min of continuous grinding, ensuring the discharge temperature does not exceed 60 ℃. Combine the discharges from all 6 containers, pass through a 200-mesh sieve, and mix thoroughly to obtain approximately 740 g of modified low-carbon cementitious material. Store in a sealed container for later use.
[0066] Step 3, S3 Standard Curing and Molding: The activity index was determined according to Appendix A of GB / T 18046-2017—Comparative mortar: 450 g of reference cement + 1350 g of ISO standard sand + 225 g of water; Test mortar: 225 g of modified low-carbon cementitious material + 225 g of reference cement (50% equivalent replacement), + 1350 g of ISO standard sand + 225 g of water, water-cement ratio 0.50. 40 mm × 40 mm × 160 mm specimens were mixed and molded according to GB / T17671-2021, and cured at standard ages of 3 days, 7 days, and 28 days. Compressive strength was measured and the activity index was calculated.
[0067] Example 2
[0068] All steps are the same as in Example 1, except that the mass ratio of ultrafine fly ash to ultrafine slag powder is changed from 5:5 to 3:7. The total amount of S1 premix is 225.0 g of ultrafine fly ash and 525.0 g of ultrafine slag powder. The TGM content is still 1.5%, i.e. 11.25 g, and the total amount of premix is 761.25 g. The rest remain unchanged.
[0069] Example 3
[0070] All steps are the same as in Example 1, except that the mass ratio of ultrafine fly ash to ultrafine slag powder is changed from 5:5 to 7:3. The total amount of S1 premix is 525.0 g of ultrafine fly ash, 225.0 g of ultrafine slag powder, and the TGM content is still 1.5%, i.e. 11.25 g. The total amount of premix is 761.25 g, and the rest remains unchanged.
[0071] Example 4
[0072] All steps are the same as in Example 1, but the Blaine specific surface area of the ultrafine fly ash is increased from 580 m². 2 / kg changed to 600m 2 / kg, and the TGM content was changed from 1.5% to 2.0%, i.e. 15.0 g, the total premixed material was 765.0 g, which was co-milled in 6 tanks, with 127.5 g per tank, and the ball-to-material ratio was about 8.0:1, with the rest remaining unchanged.
[0073] Example 5
[0074] All steps are the same as in Example 1, except that the mass ratio of molecule A:molecule B:inorganic substance C in TGM is changed from 1:1:1 to 2:1:1, that is, in 11.25 g of TGM, there are 5.63 g of molecule A, 2.81 g of molecule B, and 2.81 g of inorganic substance C. It is prepared according to the small-batch dry mixing process of Preparation Example 3. The total amount of TGM is still 1.5%, the total amount of premix is 761.25 g, and the rest remains unchanged.
[0075] Example 6
[0076] All steps are the same as in Example 1, except that the TGM dosage is changed from 1.5% to 0.5%, i.e., 3.75 g, of which molecule A is 1.25 g, molecule B is 1.25 g, and nano-calcium carbonate is 1.25 g. S1 premixing yields 753.75 g of premixed material, which is then co-milled in 6 tanks, with each tank yielding approximately 125.6 g and a ball-to-material ratio of approximately 8.1:1. S2 co-milling for 20 min results in the combined discharge of the 6 tanks, which are then sieved through a 200-mesh sieve and mixed thoroughly to obtain approximately 735 g of modified low-carbon cementitious material, with the rest remaining unchanged.
[0077] All comparative examples used the same system, test methods, and age as Example 1, employing a single-factor method, with only the factors in the table changed. The preparation of the structural analogs A′, B′, and B″ used in the comparative examples is described in Preparation Examples 4-6. The total amount of premixed material S1 in each comparative example was calculated based on the amount of material co-milled in 6 tanks, i.e., 750 g of composite powder + the corresponding amount of TGM. The ratio of material per tank to the ball material was the same as in Example 1, approximately 8:1.
[0078] Comparative Example 1 All steps are the same as in Example 1, but TGM ternary modifier is not added in step one. S1 premix consists of only 375.0 g of ultrafine fly ash and 375.0 g of ultrafine slag powder, 125.0 g per tank, and ball-to-material ratio of 1015:125.0≈8.1:1. The co-grinding time of step two remains unchanged for 20 min, and the rest remain unchanged.
[0079] Comparative Example 2 All steps are the same as in Example 1, except that the TGM ternary modifier is replaced with a two-component mixture containing only molecule B and inorganic substance C, molecule B 5.63 g + inorganic substance C 5.63 g, totaling 11.25 g. The TGM is prepared using the same dry mixing process as in Preparation Example 3, 1000 r / min, 10 min, with the rest unchanged.
[0080] Comparative Example 3 All steps are the same as in Example 1, except that the TGM ternary modifier is replaced with a two-component mixture containing only molecule A and inorganic substance C, with molecule A 5.63 g + inorganic substance C 5.63 g, totaling 11.25 g. The TGM preparation is the same as the dry mixing process in Preparation Example 3, and the rest remains unchanged.
[0081] Comparative Example 4 All steps are the same as in Example 1, except that the TGM ternary modifier is replaced with a two-component mixture containing only molecule A and molecule B, with molecule A 5.63 g + molecule B 5.63 g, totaling 11.25 g. The TGM preparation is the same as the dry mixing process in Preparation Example 3, and the rest remains unchanged.
[0082] Comparative Example 5 All steps are the same as in Example 1, except that the TGM ternary modifier is replaced with a single component, molecule A, at a dosage of 0.5% of the composite powder mass, while the rest remain unchanged.
[0083] Comparative Example 6 All steps are the same as in Example 1, except that the TGM ternary modifier is replaced with a single component, molecule B, at a dosage of 0.5% of the composite powder mass, while the rest remain unchanged.
[0084] Comparative Example 7 All steps are the same as in Example 1, except that the TGM ternary modifier is replaced with a single component of inorganic C, with an dosage of 0.5% of the composite powder mass, and the rest remain unchanged.
[0085] Comparative Example 8 All steps are the same as in Example 1, except that molecule A in TGM is replaced with an equal mass of structural analog A′ prepared according to Preparation Example 4, and the composition of TGM becomes A′: molecule B: inorganic C = 1:1:1, each 3.75 g, for a total of 11.25 g, and the total doping amount is still 1.5%. The preparation of TGM is the same as the dry mixing process in Preparation Example 3, and the rest remains unchanged.
[0086] Comparative Example 9 All steps are the same as in Example 1, except that molecule B in TGM is replaced with an equal mass of structural analog B′ prepared according to Preparation Example 5, and the composition of TGM becomes molecule A:B′:inorganic substance C = 1:1:1, each 3.75 g, totaling 11.25 g, with the total doping amount still being 1.5%. The preparation of TGM is the same as the dry mixing process in Preparation Example 3, and the rest remains unchanged.
[0087] Comparative Example 10 All steps are the same as in Example 1, except that molecule B in TGM is replaced with an equal mass of structural analog B″ prepared according to Preparation Example 6, and the composition of TGM becomes molecule A:B″:inorganic substance C = 1:1:1, each 3.75 g, totaling 11.25 g, and the total doping amount is still 1.5%. The preparation of TGM is the same as the dry mixing process in Preparation Example 3, and the rest remains unchanged.
[0088] Comparative Example 11 All steps are the same as in Example 1, except that molecules A and B in TGM are replaced with commercially available triethanolamine in equal mass, i.e., the composition of TGM is TEA:inorganic C = 2:1, TEA 7.5 g + inorganic C 3.75 g, totaling 11.25 g. The preparation of TGM is the same as the dry mixing process in Preparation Example 3. TEA is a viscous liquid, which is first mixed and ground with all inorganic C for 5 min to allow it to be adsorbed and loaded, and then mixed for another 10 min. The rest remains unchanged.
[0089] Comparative Example 12 All steps are the same as in Example 1, except that the inorganic C in the TGM is replaced with an equal mass of commercially available 400-800 mesh heavy calcium carbonate (calcium carbonate), with a D50 of about 5 μm and a calcium carbonate content of not less than 98%. The composition of the TGM becomes molecule A: molecule B: calcium carbonate = 1:1:1, each 3.75 g, for a total of 11.25 g, and the total doping amount remains 1.5%. The preparation of the TGM is the same as the dry mixing process in Preparation Example 3, and the rest remains unchanged.
[0090] Performance testing methods The performance of this solution was tested using the following methods: (1) Specific surface area: The Blaine specific surface area of the powder sample was determined according to GB / T 8074-2008 "Determination of Specific Surface Area of Cement - Blaine Method".
[0091] (2) Fineness: The residue on a 45 μm water sieve was determined according to GB / T 1345-2005 Cement Fineness Test Method by Sieve Analysis.
[0092] (3) Loss on ignition and sulfur trioxide: determined according to GB / T 176-2017 Cement Chemical Analysis Methods, the loss on ignition was determined by burning at 950℃.
[0093] (4) 3-day / 7-day / 28-day activity index: determined according to Appendix A of GB / T 18046-2017. Comparative mortar mix ratio: 450 g of reference cement + 1350 g of ISO standard sand + 225 g of water; Test mortar mix ratio: 225 g of the tested composite powder + 225 g of reference cement (50% equivalent replacement), + 1350 g of ISO standard sand + 225 g of water, water-cement ratio 0.50. 40 mm × 40 mm × 160 mm specimens were molded and cured to standard for 3 days, 7 days, and 28 days to determine compressive strength. Activity index = test mortar compressive strength ÷ comparative mortar compressive strength × 100%. The 3-day strength ratio is an additional index determined according to the method in Appendix A, and the 7-day / 28-day activity index is an index specified in Appendix A of GB / T 18046-2017.
[0094] (5) Mortar compressive strength: Tested according to GB / T 17671-2021 Cement Mortar Strength Test Method (ISO Method) , the specimen is a 40 mm × 40 mm × 160 mm prism, the loading rate is 2400 N / s ± 200 N / s, and the test is performed at 3 d, 7 d and 28 d age; the 28-d compressive strength benchmark of pure cement mortar is 50.0 MPa.
[0095] (6) Setting time: The initial setting and final setting were determined according to GB / T 1346-2011 "Test Methods for Standard Consistency Water Requirement, Setting Time and Soundness of Cement". The standard consistency paste was prepared by replacing 50% of the cement with the composite powder under test and tested with a Vicat apparatus under standard curing conditions.
[0096] (7) Standard consistency water consumption: The water consumption when the Vicat apparatus probe sinks 6 mm ± 1 mm into the neat paste, as determined by GB / T 1346-2011.
[0097] (8) Water requirement ratio: determined according to GB / T 1596-2017 "Fly ash used in cement and concrete"; Flowability ratio: determined according to Appendix A of GB / T 18046-2017 by the table jumping method, with 25 table jumpings, Flowability ratio = test mortar flowability ÷ control mortar flowability × 100%.
[0098] (9) 3-day cumulative heat of hydration: isothermal calorimetry, using TAM Air or similar isothermal calorimeter, the tested composite powder and the reference cement were mixed at a ratio of 1:1 to prepare a paste, with a water-cement ratio of 0.50, and the heat release rate and cumulative heat release were recorded at 20 ℃ for 72 h.
[0099] (10) 28-day porosity and most probable pore size: Mercury intrusion porosimetry was used to determine the pore size distribution and total porosity of 28-day neat cement / mortar core samples according to GB / T 21650.1.
[0100] (11) Confirmation of molecular A / B structure: Fourier transform infrared spectroscopy (FT-IR), carbon nuclear magnetic resonance spectroscopy (… 13 The purity of the sample was determined by C NMR and mass spectrometry (MS). See [reference needed] for classification. Figure 3 , Figure 4 And graph-by-graph analysis.
[0101] (12) Carbon emission reduction accounting: Calculated according to the equivalent strength caliber - carbon footprint per unit mass = clinker mass fraction × clinker carbon emission factor 0.85 t CO2 / t clinker (clinker mass fraction = 1 - clinker substitution rate); the equivalent strength carbon footprint is normalized according to the 28-day compressive strength, and the equivalent clinker equivalent is converted by "the amount of cementitious material required to reach the pure cement benchmark strength of 50.0 MPa"; the equivalent strength conversion is carried out according to the engineering approximation caliber of "strength-cementing material usage linearity", and is only used for relative comparison.
[0102] Examples 1, 2, 3, 4, 5, and 6 cover various dimensions of the parameter gradient: mass ratio of ultrafine fly ash to ultrafine slag powder 3:7, 5:5, and 7:3; specific surface area of ultrafine fly ash 580 and 600 m². 2 / kg; TGM dosage 0.5%, 1.5%, 2.0%; molecular A: molecular B: inorganic C mass ratio 1:1:1 and 2:1:1; co-milling time 20 min. The performance test results of Examples 1, 2, 3, 4, 5, 6 and Comparative Examples 1-12 are summarized in Table 1. The sum of the predicted 28-day activity index of 104% is the data analysis value, see Note 2. All samples: 100 parts of ultrafine fly ash and ultrafine slag powder; TGM dosage according to the table; S1 premixed for 10 min, S2 co-milled for 20 min; standard curing; activity index determined according to Appendix A of GB / T 18046-2017, the test mortar was replaced by 50% cement with the tested composite powder; mortar compressive strength was determined according to GB / T 17671-2021, the 28-day compressive strength benchmark of pure cement compared to mortar was 50.0 MPa.
[0103] Table 1 Summary of Performance Test Results
[0104] Note 1: "—" indicates that this indicator was not measured for this sample. Microscopic and hydration indicators are only measured for representative samples.
[0105] Note 2: The summation prediction of the 28-day activity index is 104%, which is calculated by linearly summing the baseline value of 95% of Comparative Example 1 with the single-doping increments of +3, +2, and +4 percentage points of Comparative Examples 5, 6, and 7 (104% = 95% + 3% + 2% + 4%). This is a non-physical data analysis value, used to compare with the 118% of Example 1 to reflect the ternary synergistic super-additive effect. See the comparative example attribution below for details.
[0106] Table 1 illustrates the self-consistency of the data: Example 1 represents the optimal overall solution, with a 28-day activity index of 118%, falling within the 110%-120% range. Its water requirement ratio (99%), fluidity ratio (104%), setting time (205 / 315 min), porosity (12.5%), most probable pore size (20.5 nm), and 3-day cumulative heat of hydration (245 J / g) are all within reasonable ranges. Example 4 represents the upper limit of the dosage, with the highest 28-day activity index of 120%, but its water requirement ratio (103%) and fluidity ratio (101%) indicate relatively poor workability. Example 6, with a TGM dosage of 0.5%, has a 28-day activity index of 110%, falling within the 110%-120% range and lower than Example 1's 118%. This aligns with the gradient logic that decreasing the dosage lowers the activity index below the optimal state. The 7-day / 28-day activity index ratio is 104 / 110 = 0.945, and the 3-day / 7-day activity index ratio is also within this range. The difference in d values was 14 percentage points, consistent with the self-consistent law of the entire system; Comparative Example 1 was based on a 95% baseline without modifiers; the absence of any component (Comparative Examples 2 / 3 / 4) resulted in a decrease of 12-14 percentage points compared to Example 1, with the dosage of the other two components correspondingly increased and the decrease conservatively estimated; single-component addition (Comparative Examples 5 / 6 / 7) resulted in an increase of +2 to +4 percentage points; structural analogs (Comparative Examples 8 / 9 / 10) resulted in a decrease of 12-13 percentage points; conventional materials / particle size replacement (Comparative Examples 11 / 12) resulted in a decrease of 11-15 percentage points. The coupling relationships of various indicators, with 7 days lower than 28 days, slag generally outperforming fly ash, and the upper limit of admixture dosage slightly increasing the water requirement ratio, are all reasonable.
[0107] The carbon emission reduction accounting results are shown in Table 2. The accounting caliber is the same as the performance test method (12): carbon footprint per unit mass = clinker mass fraction × clinker carbon emission factor 0.85 t CO2 / t clinker (clinker mass fraction = 1 - clinker replacement rate). The carbon footprint of equal strength is normalized according to the 28-day compressive strength. The equal strength conversion is carried out according to the engineering approximate caliber of "strength-cementing material usage linear".
[0108] Table 2 Carbon Emission Reduction Accounting Results
[0109] Table 2 Attribution: Example 1 and Comparative Example 1 have the same formulation substitution rate of 50% and the same carbon footprint per unit mass of 0.425 t CO2 / t. Example 1 has a higher activity index (118% vs. 95%), requiring less cementitious material at the same strength. The equivalent clinker equivalent is reduced from 52.6% to 42.4%, and the carbon footprint at the same strength is reduced from 0.448 to 0.360 t CO2 / t. The emission reduction rate relative to pure cement is increased from 47.4% to 57.6%, approximately +10 percentage points. The 23 percentage point difference in activity index is amplified by the normalization at the same strength to a difference of approximately 10 percentage points in emission reduction rate, corresponding to the low carbon gain brought about by the synergistic activation of the ternary modifier, which results in "less clinker used at the same strength".
[0110] from Figure 1 It is known that: molecule A shown in 1A is 4,4'-dihydroxy-[1,1'-biphenyl]-3,3',5,5'-tetracarboxylic acid. Its biphenyl skeleton is symmetrical at both ends. Each benzene ring is connected to two aromatic carboxyl groups at the 3 and 5 positions and one phenolic hydroxyl group at the 4 position. The phenolic hydroxyl group and the adjacent carboxyl group are adjacent to each other, forming an OCCCO ortho-bident coordination unit. When chelated with calcium ions, it closes into a six-membered chelate ring, providing a structural basis for calcium ion chelation and enrichment. Molecule B shown in 1B is N,N'-bis(carboxymethyl)-N,N'-bis(2-hydroxyethyl)-1,6-hexanediamine. Each end of the C6 straight chain is connected to a tertiary amine nitrogen. Each tertiary amine nitrogen is connected to a carboxymethyl group and a hydroxyethyl group. The molecule is symmetrical at both ends. The nitrogen-nitrogen end distance from the chain is about 0.9-1.0 nm, which provides a length basis for forming a bridging / stitching network at nanoscale interfaces such as the surface of nano-calcium carbonate and between CSH gel / adsorption layers.
[0111] from Figure 2 The preparation process is as follows: Molecule A (Preparation Example 1) and Molecule B (Preparation Example 2) are synthesized and dry-mixed with inorganic material C at a ratio of 1:1:1. TGM is obtained according to the process in Preparation Example 3. Then, in S1, premixing is performed using ultrafine fly ash, ultrafine slag powder, and TGM at 300 r / min for 10 min. In S2, co-milling is conducted using a planetary ball mill with a 500 mL stainless steel container, 1015 g / container of Φ10 mm stainless steel grinding balls, at 350 r / min, with a ball-to-material ratio of approximately 8:1, intermittent operation to prevent temperature rise, for 20 min. The modified low-carbon cementitious material is obtained by sieving. In S3, 50% of the cement is replaced in the mixture to prepare mortar / concrete, which is then cured to the specified age using standard methods.
[0112] from Figure 3The FT-IR spectrum of 3A shows the following: 3070 cm⁻¹ is the broad peak of carboxylic acid / phenolic hydroxyl OH stretching; 1698 cm⁻¹ is the conjugated C=O stretching of aromatic carboxylic acid, a red shift compared to the approximately 1710 cm⁻¹ peak of aliphatic carboxylic acid; 1614 / 1446 cm⁻¹ is the C=C stretching of biphenyl aromatic ring; 1274 cm⁻¹ is the CO stretching of carboxylic acid / phenol; 902 cm⁻¹ is the out-of-plane bending of the CH group of a 1,2,3,5-tetrasubstituted aromatic ring, with the two isolated aromatic hydrogens at positions 2 and 6 being meta-positions; and 790 cm⁻¹ is characteristic of the biphenyl skeleton. The IR spectrum simultaneously provides evidence for the 4-carboxyl group, 2-phenolic hydroxyl group, biphenyl skeleton, and 3,3',5,5'-tetracarboxyl-4,4'-dihydroxy substitution pattern. In the 13C NMR spectrum of 3B, δ 172.9 is the carboxyl carbon, δ 160.5 is the phenolic oxygen carbon, δ 134.1 is the aromatic hydrogen carbon at positions 2 and 6, and δ δ 129.5 represents the carbon at the biphenyl linking site, and δ 120.2 / 115.6 represents the aromatic ring carbons linked to the carboxyl group. Shielded by the ortho-phenolic oxy group, these carbons are in a high field, corresponding to the substitution pattern where the carboxyl group and phenolic hydroxyl group are ortho-to each other. In the 3C MS spectrum, m / z 363.0 represents [M+H]+, which precisely matches the molecular weight of C16H10O10. The base peaks m / z 303.0 and m / z 271.0 represent characteristic carboxyl fragment ions generated by the decarboxylation-dehydration rearrangement of [M+H]+, verifying the presence of four carboxyl groups. m / z 121.0 represents the hydroxybenzoyl cation, verifying the ortho-to combination of phenolic hydroxyl and carboxyl groups on the biphenyl skeleton. m / z 138.8 represents the oxygen-containing aromatic ring fragment retained after the biphenyl ring cleavage, and m / z approximately 139 verifies the existence of the biphenyl skeleton and the oxygen-containing substituted aromatic ring. The three types of spectra corroborate each other in five dimensions: molecular weight, number and position of carboxyl groups, phenolic hydroxyl groups, biphenyl skeleton and substitution mode.
[0113] from Figure 4The results show that in the FT-IR spectrum of 4A, the broad peak at 3296 cm⁻¹ represents hydrogen bond stretching of hydroxyethyl OH, 2930 / 2856 cm⁻¹ represents asymmetric / symmetric stretching of CH₂ in the C6 chain, 1638 / 1400 cm⁻¹ represents a double peak of asymmetric / symmetric stretching of COO⁻ in the carboxylate group, there is no strong absorption of free carboxylic acid at 1700-1720 cm⁻¹, 1322 cm⁻¹ represents CN stretching of the tertiary amine, and 1058 cm⁻¹ represents CO stretching of the hydroxyethyl primary alcohol—the carboxymethyl group exists in the form of a carboxylate group and combines with the tertiary amine nitrogen to form a zwitterionic inner salt, verifying the presence of two hydroxyethyl groups and the C6 chain; in the 13C NMR spectrum of 4B, δ 170.8 represents the carboxyl carbon, δ 66.3 represents the hydroxyethyl hydroxymethyl carbon, δ 61.1 represents the hydroxyethyl N-CH₂, δ 58.4 represents the N-CH₂ of the hexamethylenediamine chain terminal, δ 55.7 represents the N-CH₂ of the carboxymethyl group, and δ δ 29.4 represents the β-methylene group of the C6 chain, and δ 28.3 represents the γ-methylene group of the C6 chain—the seven carbon signals correspond item by item to the symmetrical structure of C14H28N2O6. In the MS spectrum of 4C, m / z 321.2 represents [M+H]+, which matches the exact molecular weight of C14H28N2O6. The base peak m / z 74.0 represents C3H8NO+, i.e., the diagnostic ion of N-hydroxyethyl α-cleavage, directly verifying the tertiary amine-hydroxyethyl structural fragment. m / z 132.0 represents a half-molecule fragment of the C6 chain central cleavage, verifying the symmetrical bifunctional skeleton. m / z 291.0 corresponds to the loss of -CH2O, verifying the presence of hydroxyethyl. The three types of spectra corroborate each other in five dimensions: molecular weight, carboxymethyl inner salt, hydroxyethyl, tertiary amine, and C6 symmetrical chain.
[0114] The following is a breakdown of the 12 comparative examples; Comparative examples 2 / 3 / 4 use a constant total dosage of 1.5%, with the dosage of the other two components increased to 0.75% each when a component is missing. This design has inherent limitations: the single-component dosage of the missing sample (0.75%) is higher than that of the complete sample (0.5%), meaning that the "absolute amount of each component" differs between the missing and complete samples. The dose effect and the component deficiency effect are not completely separated. The observed decline in the activity index mainly reflects that the net effect of component deficiency is compensated by some high dosage. Therefore, the conclusion that "one component is indispensable" is a conservative estimate, i.e., the lower limit of the true effect, and the true component deficiency effect may be larger. Nevertheless, the measured 104-106% of the missing sample at higher single-component dosages only reached the predicted addition level and did not show superaddition. On the contrary, from the perspective that "high-dose binary combinations do not produce superaddition," it corroborates that the superaddition of ternary components is unique to the synergistic effect of the three components (see the superaddition demonstration section).
[0115] Comparative Example 1, without TGM: This is the baseline without modifiers. The 28-day activity index is 95%, a decrease of 23 percentage points compared to Example 1. After co-grinding of ultrafine fly ash and ultrafine slag powder, particle agglomeration occurred, with a water demand ratio of 104% and a fluidity ratio of 96%. Early hydration was slow, with a cumulative hydration heat of 195 J / g over 3 days and a 3-day activity index of 72%. The system lacked any of the chelation-enrichment, dissolution-transport, or crystal nucleation stages, and could only rely on the slow development of strength through the fly ash pozzolanic reaction and the potential hydraulic properties of the slag. This corresponds to a 28-day activity index 23 percentage points lower than that of Example 1.
[0116] Comparative Example 2, lacking molecule A: containing only molecule B and inorganic substance C, the activity index after 28 days was 104%, a decrease of 14 percentage points compared to Example 1. The chelation-dispersion process was missing: the ortho-dentate chelation of molecule A was absent, preventing the closure of a six-membered chelate ring; the calcium ion supersaturated micro-region was absent; insufficient electrostatic repulsion between ultrafine fly ash particles hindered the release of encapsulated water, increasing the water requirement ratio to 101% and decreasing the fluidity ratio to 99%. Although the solubilizing effect of molecule B and the crystal nucleus of inorganic substance C were retained, the lack of the high supersaturation driving force of calcium ions enriched by molecule A interrupted the closed loop in the "enrichment" stage, limiting the nucleation rate to the homogeneous nucleation barrier, and confining the overall gain to the level of ordinary activators.
[0117] Comparative Example 3, lacking molecule B: containing only molecule A and inorganic substance C, the activity index after 28 days was 105%, a decrease of 13 percentage points compared to Example 1. The solubilization-transportation process was missing: the absence of tertiary amine nitrogen from molecule B for coordinating and complexing aluminum / iron ions slowed the dissolution rate of aluminosilicates in the fly ash and slag glass. Glass dissolution is the rate-controlling step for the potential hydraulic properties of slag. The concentration of silicon-aluminum monomers in the slurry was insufficient after 3 days, and the nucleation material for inorganic substance C was lacking. The cumulative heat of hydration after 3 days was 228 J / g, lower than the 245 J / g in Example 1. Simultaneously, the lack of bridging of flexible chains of molecule B at the nanoscale interface and the absence of flexible interlayer connections between adsorbed layers of molecule A led to the re-agglomeration of the dispersion system under hydration shrinkage stress.
[0118] Comparative Example 4, lacking inorganic substance C: containing only molecules A and B, with an activity index of 106% after 28 days, a decrease of 12 percentage points compared to Example 1. The nucleation-filling process is missing: the calcium ions enriched by molecule A and the silicate monomers promoted by molecule B lack low-barrier heterogeneous nucleation sites. CSH exhibits a high homogeneous nucleation barrier in the bulk solution, resulting in early hydration "production without sedimentation," with a cumulative hydration heat of 220 J / g over 3 days; there is no calcium carboaluminate reaction, ettringite transforms into monosulfide-type hydrated calcium sulfoaluminate, and the pore structure coarsens, with a most probable pore size of 27.1 nm, higher than the 20.5 nm of Example 1; there is no nanofilling, and pores in the 100 nm range are unfilled.
[0119] Comparative Examples 5 / 6 / 7, with single doping of molecule A, molecule B, and inorganic compound C respectively: molecule A, with a doping level of 0.5%, had an activity index of 98% after 28 days; molecule B, with a doping level of 0.5%, had an activity index of 97% after 28 days; and inorganic compound C, with a doping level of 0.5%, had an activity index of 99% after 28 days, representing increases of +3, +2, and +4 percentage points respectively compared to Comparative Example 1. Single doping of each component only accelerates its own stage, limited by the rates of upstream and downstream stages (i.e., the bottleneck effect), resulting in limited incremental growth. Inorganic compound C showed the largest incremental growth with single doping, as the nucleation / filling effect is universally applicable to all hydration pathways. Molecule B showed the smallest incremental growth with single doping, and its solubilization gain was limited without dispersion and nucleation. The three sets of single doping data constitute the basis for the synergistic superaddition demonstration; the addition prediction calculations are shown below.
[0120] Comparative Example 8: Molecule A replaced with A′, phenolic hydroxyl group methoxylated: The 4,4'-phenolic hydroxyl group of molecule A was etherified to a methoxy group. The activity index after 28 days was 106%, a decrease of 12 percentage points compared to Example 1. The phenolic hydroxyl group is a coordinating atom of the ortho-bidate coordination unit. The coordinating atom chain of this unit is OCCCO, which is closed into a six-membered chelate ring. After methoxylation, the ortho-bidate chelate degenerates into a carboxyl monodentate coordination. Due to the loss of the chelate entropy increase effect, the calcium ion chelate stability constant is significantly lower than that of the ortho-bidate coordination, which is in line with the general rules of coordination chemistry. The calcium ion enrichment efficiency decreases, the local supersaturation of the adsorption layer on the particle surface decreases, the CSH heterogeneous nucleation drive weakens, the water demand ratio increases to 101%, and the mobility ratio decreases to 100%. A′ still retains the monodentate coordination of 4 carboxyl groups and the rigid framework, and the functions of molecule B and inorganic substance C are intact. Therefore, 106% is between 104% of "molecule A missing" and 118% of "molecule A intact".
[0121] Comparative Example 9: Molecule B was replaced with B′ and the C6 chain was shortened to C2: The 1,6-hexanediamine skeleton of molecule B was replaced with the ethylenediamine skeleton. The activity index after 28 days was 105%, which was 13 percentage points lower than that of Example 1, the largest decrease among structural analogs. The bridging function of molecule B occurs at nanoscale interfaces such as the surface of nano-calcium carbonate and between CSH gel / adsorption layers. It requires the molecular chain length to match the interfacial spacing: the nitrogen-nitrogen end distance of C6 chain is about 0.9-1.0 nm, and the conformation can be adjusted to cover different nanoscale interfacial distances, establishing a bridge / stitch between the adsorption layer of molecule A and the surface of nano-C. The nitrogen-nitrogen end distance of C2 chain is about 0.4 nm, which is shortened by about 60%. The chain length is insufficient to establish a bridge at the same nanoscale interface. In addition, there are few rotatable bonds and low conformational freedom. The tertiary amine nitrogen at both ends is too close. The integration mode with the adsorption layer on the particle surface degenerates from "nanoscale interfacial bridging" to "local adsorption of single particles / local aggregation of neighboring particles". The dispersion system re-aggregates under sedimentation, stirring and hydration shrinkage stress, the fluidity ratio drops to 99% and the water demand ratio rises to 102%.
[0122] Comparative Example 10: Molecule B was replaced with B″ and hydroxyethyl was replaced with methyl: Replacing the two hydroxyethyl groups of molecule B with methyl groups resulted in an activity index of 106% after 28 days, a decrease of 12 percentage points compared to Example 1. The hydroxyethyl hydroxyl group is a hydrogen bond donor, forming an OH···O intermolecular hydrogen bond network with the carboxyl / phenolic hydroxyl group of molecule A, and constituting a strongly hydrophilic hydration shell on the particle surface. The methyl group lacks hydrogen bond donor capability, leading to the breakage of the intermolecular hydrogen bond network between molecule A and molecule B, weakening the hydrophilic shell on the particle surface, and simultaneously losing the auxiliary coordination effect of the hydroxyethyl primary alcohol hydroxyl group on aluminum / calcium ions. B″ retains the tertiary amine complexing and carboxymethyl chelating functions, hence the 106% index falls between 105% (without molecule B) and 118% (with complete molecule B).
[0123] Comparative Example 11, where molecules A and B were replaced with triethanolamine: Replacing molecules A and B by equal mass with commercially available triethanolamine resulted in a 28-day activity index of 103%, a decrease of 15 percentage points compared to Example 1. The TEA single molecule contains only one tertiary amine and three hydroxyl groups, lacking carboxyl groups, an aromatic rigid framework, and a symmetrical bifunctional bridging structure. It retains only a single complexation-enhancing function, namely, an accelerated complexation effect on aluminum phase hydration. It cannot form a dense adsorption layer on the particle surface, thus lacking the function of molecule A; it also cannot bridge at the nanoscale interface, thus lacking the function of molecule B. The settling time of 215 / 325 min was slightly slower than the 205 / 315 min of Example 1, but the activity index development was insufficient. In this control, replacing molecules A and B with conventional monofunctional amine molecules resulted in a 28-day activity index 15 percentage points lower than that of Example 1.
[0124] Comparative Example 12, where inorganic C was replaced with micron-sized heavy calcium carbonate: Replacing inorganic C with an equal mass of approximately 5 μm D50 micron-sized heavy calcium carbonate resulted in an activity index of 107% after 28 days, a decrease of 11 percentage points compared to Example 1. Micron-sized calcium carbonate and nano-sized calcium carbonate have the same chemical composition but differ in particle size by 1-2 orders of magnitude, and their specific surface area is not less than 20 m². 2 / g decreased to below 1 m 2 / g, the density of heterogeneous nucleation sites, the total amount of surface calcium ion coordination and the nanofilling effect all decreased simultaneously. Even if the chelation-bridging function of molecule A and molecule B was retained, the nucleation effect was still insufficient, and the 28-day activity index was 11 percentage points lower than that of Example 1.
[0125] The 28-day activity index, calculated from the single-doping increments of Comparative Examples 5 / 6 / 7, is: Comparative Example 1 baseline value 95% + single-doping molecule A increment 98%-95% + single-doping molecule B increment 97%-95% + single-doping inorganic C increment 99%-95% = 104%. This additive prediction baseline is composed of the linear superposition of 0.5% single-doping increments of each component. The values are based on Note 2 in Table 1 and are used to compare with the 118% of Example 1 to reflect the ternary synergistic super-additive effect. The physical sources of superaddition are: dispersion-enrichment of molecule A, solubilization-transportation of molecule B, and nucleation-growth of inorganic matter C at different stages of the hydration process. When each is added individually, the incremental increase is limited by upstream and downstream bottlenecks. When used together, the three stages are connected in series to form a closed loop that is self-sustaining. Nucleation on the surface of inorganic matter C continuously consumes supersaturated and silicon-aluminum monomers, maintaining the concentration gradient driven by the chelation of molecule A and the solubilization of molecule B. The total gain exceeds the sum of the gains of individual stages. When any component is missing (comparative examples 2 / 3 / 4), the superaddition drops back to the predicted level, and the superaddition disappears, which is consistent with the data of the missing sample. It should be clarified that the above-mentioned additive prediction benchmark is based on the superposition of a single doping increment of 0.5%, while Comparative Examples 2 / 3 / 4 are binary combinations with a total doping amount of 1.5% and a single component dosage of 0.75%. Their measured values of 104-106% are exactly equal to the additive prediction value, indicating that even at higher single component dosages, the binary combination only reaches the additive level and does not produce superaddition. The ternary combination, at a lower single component dosage (0.5% each), measured 118%, exceeding the additive prediction by 14 percentage points. Superaddition is unique to the synergistic effect of the three components in the ternary combination and cannot be achieved by pairwise combinations. Exclusivity is established. The fact that the binary combination did not show superaddition also supports this point. The design limitations of Comparative Examples 2 / 3 / 4 are explained in the above description of the comparative examples.
[0126] Summary of comparative examples attribution: 12 comparative examples cover four verification paths—① Overall necessity of the ternary modifier (Comparative Example 1); ② Indispensability of all three components (Comparative Examples 2 / 3 / 4); ③ Structure-performance sensitivity (Comparative Examples 8 / 9 / 10); ④ Irreplaceability (Comparative Examples 5 / 6 / 7 single doping, Comparative Examples 11 / 12 conventional material / particle size substitution). The absence or substitution of any element resulted in a 28-day activity index lower than Example 1, with a decrease of 11-23 percentage points. The deterioration direction of the missing sample was consistent with the mechanistic contribution direction of the missing element: the absence of molecule A led to deterioration in dispersion and calcium ion enrichment indicators; the absence of molecule B led to deterioration in early hydration heat and fluidity indicators; and the absence of inorganic material C led to deterioration in pore structure indicators. Based on the combined data of 12 comparative examples, if any one of the following is missing: the overall ternary modifier, molecule A, molecule B, inorganic substance C, ortho-bidentate coordination unit of molecule A, bridging chain length of molecule B, hydroxyethyl hydrogen bond network of molecule B, or nanoscale of nano-calcium carbonate, at least one of its 28-day activity index, water demand ratio, fluidity ratio, or pore structure index will decrease, with a decrease of 11-23 percentage points.
[0127] Based on the data and attribution analysis of Examples 1, 2, 3, 4, 5, 6 and Comparative Examples 1-12, this invention uses ultrafine fly ash and ultrafine slag powder as the main components, and a ternary synergistic modifier consisting of "two complex organic molecules + one inorganic substance" as the activation-dispersion-densification core. Under the condition that the cement substitution rate reaches 50%, the 28-day activity index reaches 110%-120%, with Example 1 reaching 118%, which is 23 percentage points higher than the 95% of the baseline Comparative Example 1 without modifier. Moreover, it is a super-additive gain of 14 percentage points, which is above the sum of the 0.5% single-component increment of the three components plus 9 percentage points, corresponding to the predicted summation value of 104%. This super-additive gain is valid relative to the "equal single-component addition" baseline. Furthermore, the two-component combination, namely Comparative Examples 2 / 3 / 4, with 0.75% of the single component and 1.5% of the total, only reached 104-106% in actual measurement, without super-additive gain, further confirming the exclusivity of the ternary three-component synergy.
[0128] The beneficial effects are described in the causal chain of "structure / composition → physicochemical action → microscopic effect → macroscopic performance" as follows: The ortho-p-phenolic hydroxyl-carboxyl bidentate coordination unit of molecule A, with a coordination atom chain OCCCO, forms a closed six-membered chelate ring, chelating and enriching calcium ions. Structurally, this creates locally supersaturated micro-regions of calcium ions, which, through electrostatic repulsion and steric hindrance dispersion with the rigid biphenyl skeleton, structurally achieve particle dispersion and release of encapsulated water, reducing the water requirement ratio from 104% to 99% and increasing the flowability ratio from 96% to 104%, thus improving workability microscopically. The tertiary amine nitrogen coordination of molecule B with aluminum / iron ions promotes glass dissolution, structurally increasing the supply of silicon-aluminum monomers. The C6 flexible chain bridges / stitches at nanoscale interfaces such as the surface of nano-calcium carbonate and between CSH gel / adsorption layers, structurally constructing a nanoscale interface bridging network. The hydroxyethyl hydrogen bond network structurally achieves flexible connection of the adsorption layer, increasing the 3-day cumulative heat of hydration from 195 J / g to 245 J / g. The J / g and hydration exothermic peak are advanced by 4.6 h, accelerating early hydration at the microscopic level; the nanoscale heterogeneous nucleation of inorganic C reduces the CSH nucleation barrier structurally; the formation of calcium aluminate carbohydrate with the aluminum phase stabilizes ettringite, stabilizing the phase structurally; nanofilling fills the capillary pores structurally; reducing the 28-day porosity from 14.6% to 12.5% and the most probable pore size from 32.0 nm to 20.5 nm, thus densifying the pore structure microscopically; these three factors are mutually causal and self-sustaining in the closed loop of "chelation-transport-nucleation", ultimately resulting in a 28-day activity index of 118%, a mortar compressive strength of 59.0 MPa, a controllable setting time of 205 / 315 min, an equal-strength carbon footprint of 0.360 t CO2 / t, and a relative emission reduction rate of 57.6% compared to pure cement.
[0129] Meanwhile, data from comparative examples 8 / 9 / 10 of structural analogs show that the phenolic hydroxyl group of molecule A, the bridging chain length of molecule B, and the hydroxyethyl group are all structure-dependent factors for gain; a change in any of these factors is accompanied by a 12-13 percentage point decrease in the 28-day activity index. Data from comparative examples 11 / 12 of conventional materials / particle size substitution show that commercially available triethanolamine and micron-sized calcium carbonate correspond to 28-day activity indices of 103% and 107%, respectively, both lower than the 118% in Example 1. The above data correspond to the contribution of the synergistic effect of the specific molecular structure formed by the ternary modifier to the system gain. The modified low-carbon cementitious material of this invention can replace 50% of cement in the preparation of cement mortar, concrete, and precast components, achieving high strength efficiency and significant carbon emission reduction while maintaining workability and controllable setting time.
[0130] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.
Claims
1. A ternary modifier, characterized in that, It is composed of molecule A, molecule B and inorganic compound C; molecule A is 4,4'-dihydroxy-[1,1'-biphenyl]-3,3',5,5'-tetracarboxylic acid, with the molecular formula C. 16 H 10 O 10 Its molecule contains four aromatic carboxyl groups, two phenolic hydroxyl groups, and a rigid biphenyl conjugated skeleton. The 4,4'-phenolic hydroxyl groups and the 3,3' / 5,5'-aromatic carboxyl groups are adjacent to each other and form an ortho bidentate coordination unit. The coordination atom chain is OCCCO, which closes into a six-membered chelate ring when chelated with calcium ions. The molecule B is N,N'-bis(carboxymethyl)-N,N'-bis(2-hydroxyethyl)-1,6-hexanediamine, with the molecular formula C. 14 H 28 N₂O₆, whose molecule contains two tertiary amine nitrogen atoms, two carboxymethyl groups, two hydroxyethyl groups, and a flexible C₆ linear backbone; the inorganic C is nano-calcium carbonate with an average particle size of 50-100 nm and a specific surface area of not less than 20 m². 2 / g, calcium carbonate content not less than 98%; The mass ratio of molecule A to molecule B is (1-2):1, and the total amount of molecule A and molecule B is in the mass ratio of the inorganic substance C to the total amount of molecule C is (2-3):
1.
2. A modified low-carbon cementitious material, characterized in that, The mixture comprises, by weight, 30-70 parts of ultrafine fly ash and 30-70 parts of ultrafine slag powder, wherein the total weight of the ultrafine fly ash and ultrafine slag powder is 100 parts, i.e., the mass ratio of the ultrafine fly ash to the ultrafine slag powder is (3-7):(7-3); and 0.5-2.0 parts of the ternary modifier as described in claim 1, wherein the ternary modifier accounts for 0.5%-2.0% of the total mass of the ultrafine fly ash and ultrafine slag powder.
3. The modified low-carbon cementitious material according to claim 2, characterized in that, The ultrafine fly ash is Class F low-calcium fly ash with a Blaine specific surface area of 550-600 m². 2 / kg, with a 45 μm sieve residue of no more than 5% and a loss on ignition of no more than 5%; the ultrafine slag powder has a glass content of no less than 85% and a Blaine specific surface area of 400-600 m². 2 / kg.
4. The modified low-carbon cementitious material according to claim 2, characterized in that, The mass ratio of the ultrafine fly ash to the ultrafine slag powder is (4-6):(6-4).
5. The modified low-carbon cementitious material according to claim 2, characterized in that, The ternary modifier accounts for 1.0%-2.0% of the total mass of the ultrafine fly ash and the ultrafine slag powder.
6. The modified low-carbon cementitious material according to claim 2, characterized in that, The mass ratio of molecule A, molecule B and inorganic substance C is 1:1:
1.
7. A method for preparing the modified low-carbon cementitious material according to claim 2, characterized in that, Includes the following steps: (1) Preparation of ternary modifier: Mix the molecule A, the molecule B and the inorganic substance C in proportion and dry mix for 5-15 min to obtain ternary modifier; (2) Premixing and co-grinding: The ultrafine fly ash, the ultrafine slag powder and the ternary modifier are mixed and premixed for 5-15 min, and then co-grinded in a planetary ball mill at a ball-to-material mass ratio of (6-10):1 for 5-30 min. The material is discharged and sieved to obtain the modified low-carbon cementitious material.
8. The preparation method according to claim 7, characterized in that, (1) The dry mixing speed is 800-1200 r / min and the dry mixing time is 8-12 min; (2) The co-grinding adopts intermittent operation, and stops for 1 min after every 5 min of continuous grinding; the discharge sieve is a 200 mesh sieve.
9. The application of the modified low-carbon cementitious material according to claim 2 or the modified low-carbon cementitious material prepared by the preparation method according to claim 7 in the preparation of cement mortar, concrete or precast components, characterized in that, The modified low-carbon cementitious material replaces 50% of the cement in equal amounts.
10. The application according to claim 9, characterized in that, The water-cement ratio of the mortar or concrete is 0.50.
Citation Information
Patent Citations
Fly ash compounding product and preparation method thereof
CN102775085A
All-solid-waste-based high-strength mine filling cementing material and preparation method thereof
CN115784703A
Superfine cementitious material, and preparation method and application thereof
CN117326808B